The Principles of Brazil's Unified Health System (SUS) and Current Challenges to Ensuring Universal Access to Healthcare - Helenitta Melo da Silva Alves; Juliana Reis de Alcantara; Simonia Mara de Oliveira; Karen de Fátima Figueroa Bohórquez; Alanir Aparecida da Silva; Juliana Aparecida Pereira Ribeiro; Rene Humberto Rodrigues; Suzana Santos da Costa (RSV, 2026)
Brazil's Unified Health System (Sistema Único de Saúde-SUS) represents one of the world's largest publicly funded universal healthcare systems, providing comprehensive healthcare services to more than 200 million citizens. Established through the 1988 Federal Constitution and regulated by subsequent legislation, the SUS is founded on the principles of universality, comprehensiveness, equity, decentralization, regionalization, and social participation. These principles have enabled substantial advances in health indicators, expanded access to essential services, and reduced historical inequalities in healthcare provision. Nevertheless, the system currently faces increasingly complex challenges associated with demographic transitions, epidemiological changes, chronic underfunding, regional disparities, technological innovation, workforce shortages, judicialization of healthcare, and the growing demand for high-cost medical technologies. This academic essay critically examines the constitutional principles underlying the SUS and analyzes the contemporary barriers that threaten the effective realization of universal access to healthcare in Brazil. By integrating theoretical discussions with institutional and policy perspectives, the essay explores how structural, political, economic, managerial, and demographic factors influence the sustainability of universal health coverage. The discussion also reflects upon future strategies capable of strengthening governance, financing, digital transformation, and public management while preserving the constitutional commitment to health as a fundamental social right.